REVITALISASI PASAR TRADISIONAL DAN PERAN PEMERINTAH UNTUK MEMINIMALKAN KESENJANGAN EKONOMI - Bondan Satriawan; Syukron Abdillah (Trunojoyo University of Madura, 2011)
This paper is a conceptual paper that focuses on how to revitalize and improving the condition of Indonesian traditional market. This kind of market is facing a tight competition versus what so called modern market. Statistically there is a significant decline of the existence of traditional market and on the otherhand, modern market rises steadily over the past years. If the condition continues it is afraid that millions of people will loose their jobs. Related to that, the paper discusses how government can play a significant role to harness the situation and even can revitalize the performance of traditional market in order to survive from the competition eith modern market but still bring the positive impact and more value added to the consumers.